Breastfeeding Self-Efficacy at 24 Hours Postpartum with Inadequate Milk Production: A Case Report - Pamungkas, Mutiara Harul Aini; Astuti, Yuni; Wulandari, Noor (LPPM STIKes Muhammadiyah Ciamis, 2025)
Exclusive breastfeeding during the first six months is critical for neonatal health and development. Despite government initiatives, the exclusive breastfeeding rate in Indonesia remains below the national target of 80% as set by the Ministry of Health. One of the significant psychological determinants of successful breastfeeding is maternal self-efficacy, or the mother’s belief in her ability to breastfeed successfully. This study aimed to explore the breastfeeding self-efficacy of a postpartum mother during the first 24 hours following delivery. This case report employed a descriptive design using a nursing care approach. The Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF), consisting of 14 items rated on a 5-point Likert scale, was used to measure the mother's level of breastfeeding self-efficacy. The assessment was conducted twice: at 2 hours postpartum and again at 24 hours postpartum. The study was carried out in May 2025 at the Bougenville Room of Tidar Hospital, Magelang City. At 2 hours postpartum, the mother demonstrated a high breastfeeding self-efficacy score of 55, indicating strong confidence. However, by 24 hours postpartum, her score had decreased to 49, a moderate level, coinciding with her report of inadequate milk production. This change suggests that early lactation difficulties can negatively influence a mother’s self-confidence in breastfeeding. Inadequate breast milk production during the first 24 hours postpartum can reduce maternal breastfeeding self-efficacy. It is essential for nurses to provide education and emotional support in the early postpartum period to help mothers build confidence and improve breastfeeding outcomes.